Pengelolaan Sampah Rumah Tangga Menjadi Pupuk Organik Menggunakan Komposter di Lingkungan Desa Montong Baan Selatan, Kecamatan Sikur, Kabupaten Lombok Timur - Susilawati Susilawati; Daniel Rinengkuh Tinarja; Fedik Novibriawan; Dewi Komala Adilatussiam; Nia Audina Zein; Meta Yunia Prastika; Nina Parwati; Ratnah Ratnah; Widia Nila Risnadewi (Universitas Mataram, 2019)
Abstract: South Montong Baan Village is one of the villages in East Lombok Regency which the majority of the people there rely heavily on the agricultural sector. The problem still faced by the locals is that the lack of awareness in managing the waste. An alternative way offered to overcome the situations by educating the locals on how to make use of domestic waste and training, producing, making use, monitoring, and evaluating. The outcomes of the program held is the farmer group of South Montong Baan has potential things to produce organic fertilizer (compose) from domestic scale by using waste such as kitchen stuff and livestock manure. The results of the waste from the composter are in the forms of liquid and non-liquid which both can be applied to the plants, the fermentation process takes about 2 till 3 weeks for the fertilizer to be used. The outcomes from monitoring and evaluating showed that the application of organic fertilizer made from domestic waste can decrease the use of inorganic fertilizer which in turn can reduce the expense of the farming activities and the local farmer group has also committed in developing organic fertilizer from the domestic waste as a sustainable effort of agricultural development programs.Keywords: Composter, Domestic waste; Organic Fertilizer;